2013
DOI: 10.1103/physrevb.88.195201
|View full text |Cite
|
Sign up to set email alerts
|

Defect physics and electronic properties of Cu3PSe4from first principles

Abstract: The p-type semiconductor Cu3PSe4 has recently been established to have a direct bandgap of 1.4 eV and an optical absorption spectrum similar to GaAs [Applied Physics Letters, 99, 181903 (2011)], suggesting a possible application as a solar photovoltaic absorber. Here we calculate the thermodynamic stability, defect energies and concentrations, and several material properties of Cu3PSe4 using a wholly GGA+U method (the generalized gradient approximation of density functional theory with a Hubbard U term include… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…The obtained results using TB-mBJ, as displayed in Fig. 3, are in agreement with the previous studies employing HSE [6] and GGAþU functional [10]. As shown in Fig.…”
Section: Electronic Structuressupporting
confidence: 93%
See 1 more Smart Citation
“…The obtained results using TB-mBJ, as displayed in Fig. 3, are in agreement with the previous studies employing HSE [6] and GGAþU functional [10]. As shown in Fig.…”
Section: Electronic Structuressupporting
confidence: 93%
“…It has also been reported that Cu 3 PSe 4 exhibits sharp increase in the absorption coefficient giving the possibility of using a much thinner film in a solar cell devices. Theoretically, the calculations based on density functional theory have been Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/mssp explored to study the electronic and optical properties of Cu 3 PSe 4 by using HSE hybrid functional and GGAþU functional [6,10], while no theoretical calculations for Cu 3 PS 4 compound have been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Foster et al calculated formation energies of intrinsic point defects in Cu 3 PSe 4 using density‐functional theory . They found that the dominant defects with low formation energy are V Cu and P Se (both in the range of 0.47–0.5 eV), whereas the formation energies of other defects such as Cu P , V P and Se P are higher . Given the ionic radii of Cu (0.74 Å) and P (0.52 Å), the degree of Cu‐P anti‐site disordering in Cu 3 PSe 4 might be expected to be low.…”
Section: Zinc‐blende‐related Structures Beyond Kesterite and Stannitementioning
confidence: 99%
“…Therefore, under Cu‐poor and S/Se‐rich synthetic conditions, V Cu should be prevalent as a dominant acceptor defect, contributing to the p‐type conductivity for Cu 3 PSe 4 . The calculated Fermi level of 0.031 eV above the VBM also indicates that the majority of holes are generated from V Cu shallow (0.05–0.06 eV) acceptor defects, instead of the relatively deeper (0.08–0.17 eV) acceptor level of P Se anti‐site defects . For better understanding Cu 3 P(S,Se) 4 defect properties, the formation energy of charge‐balanced defect clusters may need to be explored as a future work.…”
Section: Zinc‐blende‐related Structures Beyond Kesterite and Stannitementioning
confidence: 99%
“…These include the conditions for and nature of thermalization under unitary * xiao.yin@colorado.edu † radzihov@colorado.edu time evolution |ψ(t) = e iĤ f t |ψ i (0) of a closed quantum system vis-á-vis eigenstate thermalization hypothesis [24,25], role of conservation laws and obstruction to full equilibration of integrable models argued to instead be characterized by a generalized Gibb's ensemble (GGE), emergence of statistical mechanics under unitary time evolution for equilibrated and nonequilibrium stationary states [26,27]. These questions of post-quench dynamics have been extensively explored in a large number of systems [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Early studies of a Feshbach-resonant Fermi gas predicted persistent coherent post-quench oscillations [30,44] and, more recently found topological nonequilibrium steady states and phase transitions [45,46]. Resonant Bose gas quenched dynamics studies date back to seminal experiments on 85 Rb [47,48], that demonstrated coherent Rabi-like oscillations between atomic and molecular condensates [49], enabling a measurement of the molecular binding energy.…”
Section: Introduction a Background And Motivationmentioning
confidence: 99%